Pengaruh Intellectual Capital, Tingkat Utang Dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Ayusanda, Della Puspita; Afandi, Agus (CV. ITTC INDONESIA, 2026)
Finance is a highly crucial factor in the sustainability and development of a company, as a sound financial condition determines the company’s ability to carry out its operations, expand its business, and face market competition. Therefore, managers bear significant responsibility in achieving corporate prosperity by maximizing firm value. Maximizing firm value is one of the company’s long-term objectives, as a high firm value reflects strong performance and enhances the confidence of investors and other stakeholders. In an effort to increase firm value, management must continuously implement improvements and innovations to create efficiency and generate optimal profits. One of the primary functions that must be effectively managed is the financial function, since appropriate financial decisions directly affect the company’s capital structure, profitability, and stability. This study aims to determine the effect of intellectual capital, debt level, and firm size on firm value in consumer non-cyclicals companies listed on the Indonesia Stock Exchange in 2019-2024. The population in this study used companies in the consumer non-cyclicals sector as many as 130 companies. The sampling method in this study used a purposive sampling method, in order to obtain a sample of 33 companies in the consumer non-cyclicals sector. Sources of data used in this study is secondary data. Data analysis was performed using Eviews 13. Simultaneous research results of intellectual capital, debt level, and firm size have an effect on firm value. Partially, intellectual capital and debt level have a significant effect on firm value, and firm size have no significant effect on firm value.